2016
DOI: 10.1016/j.gpb.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk Pathways and Functional Modules for Coronary Artery Disease Based on Genome-Wide SNP Data

Abstract: Coronary artery disease (CAD) is a complex human disease, involving multiple genes and their nonlinear interactions, which often act in a modular fashion. Genome-wide single nucleotide polymorphism (SNP) profiling provides an effective technique to unravel these underlying genetic interplays or their functional involvements for CAD. This study aimed to identify the susceptible pathways and modules for CAD based on SNP omics. First, the Wellcome Trust Case Control Consortium (WTCCC) SNP datasets of CAD and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(48 reference statements)
2
5
0
Order By: Relevance
“…The six top-ranking pathways were cyclin-dependent protein serine/threonine kinase inhibitor activity, RIG-I-like receptor signaling pathway, organophosphate ester transport, negative regulation of muscle cell differentiation, phospholipid efflux, and phospholipid transport (Figure 2). Several previously reported pathways were also replicated in our study, including low-density lipoprotein particle receptor binding, positive regulation of triglyceride metabolic process, reverse cholesterol transport, and lipoprotein metabolic pathways (Makinen et al, 2014;Ghosh et al, 2015;Zhao et al, 2016).…”
Section: Pathway-based Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…The six top-ranking pathways were cyclin-dependent protein serine/threonine kinase inhibitor activity, RIG-I-like receptor signaling pathway, organophosphate ester transport, negative regulation of muscle cell differentiation, phospholipid efflux, and phospholipid transport (Figure 2). Several previously reported pathways were also replicated in our study, including low-density lipoprotein particle receptor binding, positive regulation of triglyceride metabolic process, reverse cholesterol transport, and lipoprotein metabolic pathways (Makinen et al, 2014;Ghosh et al, 2015;Zhao et al, 2016).…”
Section: Pathway-based Analysissupporting
confidence: 84%
“…KLFs have been shown to interact with the components of atherosclerosis pathogenesis and have also been linked to metabolic abnormalities, including obesity and diabetes mellitus (Pollak et al, 2018). In line with our findings from KEGG enrichment analysis of co-expressed genes of ZNF655, Zhao et al (2016) constructed a genetic network based on gene-gene interactions and revealed that pathways involved in Alzheimer's disease, non-alcoholic fatty liver disease, and Huntington's disease were also associated with CAD risk. Moreover, Bis et al (2018) recently identified the importance of ZNF655 for transcriptional regulation in Alzheimer's disease pathogenesis through whole genome sequencing.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, Liu et al reported that the most studied multi-loci genes are those of angiotensin I converting enzyme, lipid and lipoprotein metabolism [ 1 ]. Hence, individual GWAS and meta-analyses have confirmed the speculated deterministic role of genetic predisposition in occurrence, progression of atherosclerosis and coronary plaque calcification, with multiple converging pathways, including cardiac muscle contraction, glycerolipid metabolism, and glycosaminoglycan biosynthesis [ 5 , 32 , 37 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found similar changes of COX7B, COX6A2 and UQCRQ also exist in the cardiac muscle contraction pathway. An abnormal cardiac muscle contraction pathway has a significant effect on coronary artery disease as well as cardiac hypertrophy and dysfunction 23 , 24 . The three overlapping proteins in these two pathways also provide evidence that CKD and cardiovascular disease may have some commonalities in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%